(untitled) (Ustozlar uchun, 2025)
Abstract: This article explores the significant role of a father, their life journey, the love they give and the immense strength with which they live for their families. In this article, we will delve into our father’s life stories, their outlook on the world and the difficulties they faced for the sake of their children.